Peran Tafakur Day Sebagai Upaya Pencegahan Tindakan Bullying di SMP Al-Amanah Cileunyi dalam Perspektif Hak Asasi Manusia - Diva Raya Naysila Nada; Revameila Susanti; Muhamad Syamsul Maarif; Alif Marta Nurhadi; Raihan Hadi Prama (Yayasan Al-Afif, 2025)
Bullying in the educational environment is a serious violation of children’s rights to security and protection from violence. This study aims to analyze the effectiveness and compatibility of the “Tafakur Day” disciplinary mechanism at SMP Al-Amanah Cileunyi with Human Rights principles, as well as to measure the impact of advocacy interventions in increasing students’ legal awareness. This study employs socio-legal research with a qualitative approach and social intervention involving 52 grade 9 students as role models. Data collection techniques included observation, in-depth interviews, and gamification-based post-tests. The results indicate that Tafakur Day has an educative-religious dimension through Quranic memorization methods (stages 1-3), but the social sanction stages involving public disclosure (stages 4-6) potentially violate children’s rights to privacy and dignity. Furthermore, the advocacy intervention successfully deconstructed students’ understanding of the boundaries between “jokes” and bullying. Based on the post-test evaluation, 70% of students demonstrated a good understanding of bullying parameters. This study recommends integrating the compiled bullying handling module into school policies and evaluating the public disclosure method in Tafakur Day to be more oriented towards restorative justice.